In vitro Degradation of Pure Mg for Esophageal Stent in Artificial Saliva. Issue 5 (May 2016) - Zeng, Rong-Chang; Li, Xiao-Ting; Liu, Li-Jun; Li, Shuo-Qi; Zhang, Fen
Highlights: A dense degradation product film formed on pure Mg surface immersed in artificial saliva. The degradation rate kept low and pH values insignificantly changed in the first 5 days of immersion. Pure Mg has the potential to be used as esophageal stents for its desirable degradation resistance in artificial saliva. Graphical Abstract: Abstract : Magnesium and its alloys as biodegradable implant materials can be potentially used in cardiovascular and orthopedic devices. However, few studies have focused on its application in esophageal stents. In this paper, time-lapse degradation characteristics of pure Mg were analyzed by scanning electron microscopy, energy dispersive spectroscopy, X-ray diffraction, Fourier transform infrared spectroscopy, hydrogen evolution, pH and electrochemical measurements after immersion in artificial saliva for different times. Results revealed that a dense degradation product film formed on samples, which mainly consisted of two kinds of layers: one was calcium phosphate compounds with different structures; the other was thin magnesium hydrate layer close to the substrate. Less pH increase and low degradation rate were observed in the first 5 days of immersion, which can be ascribed to the formation of a thicker and denser layer on the sample surface with increasing immersion time. And then there was an increase in degradation rate and pH values; the deposition layer remained almost intact after immersion for 6 and 8 days. After 10 days of immersion, the degradation rate and pH value remained stable, and the calcium phosphate layer was delaminated and the inner magnesium hydrate layer was exposed. This study indicated that pure Mg exhibited desirable degradation resistance in artificial saliva, which provided magnesium-based materials with the potential to be used as esophageal stents.